Cook & Cook, Japan At War - An Oral History - Goetz, William (Teaching History: A Journal of Methods, 1996)
Haruko Taya Cook and Theodore F. Cook have compiled a gripping and revealing oral history of Japan during World War II. The authors, who interviewed several hundred survivors, selected a broad cross-section of Japanese society, including staff-level military officers, enlisted men, journalists, diplomats, artists, workers, and those barely of school age at the time of the war. The translations are exquisite, allowing the voices to speak for themselves.